Pengaruh Economic Value Added (EVA) terhadap Pengungkapan Sustainability Report - Berliana Armandani (Bandung Conference Series: Accountancy, 2022)
Abstract. This study aims to determine the effect of Economic Value Added (EVA) on the disclosure of the sustainability report. The object of research used in this study is the Economic Value Added (EVA) and disclosure of the sustainability report. The subjects in this study were the banking sub-sector companies listed on the Indonesia Stock Exchange (IDX). This research method is a descriptive verification method with a quantitative approach. This study uses secondary data with a population of 45 banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. Hypothesis testing using multiple linear regression analysis, classical assumption analysis, coefficient of determination analysis, and hypothesis testing using F test and t test. This study partially shows that the results of the Economic Value Added (EVA) have a significant effect on the Sustainability Report Disclosure as measured using NOPAT and the Cost of Capital. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Economic Value Added (EVA) terhadap pengungkapan sustainability report. Objek penelitian yang digunakan dalam penelitian ini adalah Economic Value Added (EVA) dan pengungkapan sustainability report. Subjek dalam penelitian ini adalah perusahaan sub sektor perbankan yang tercatat di Bursa Efek Indonesia (BEI). Metode penelitian ini adalah metode deskriptif verifikatif dengan pendekatan kuantitatif. Penelitian ini menggunakan data sekunder dengan populasi sebanyak 45 perusahaan perbankan yang tercatat di Bursa Efek Indonesia (BEI) untuk rentang waktu 2017-2020. Pengujian hipotesis menggunakan analisis regresi linier berganda, analisis asumsi klasik, analisis koefisien determinasi, serta uji hipoetasi menggunakan uji F dan uji t. Penelitian ini secara parsial menunjukan bahwa hasil Economic Value Added (EVA) berpengaruh signifikan terhadap Pengungkapan Sustainability Report yang diukur menggunakan NOPAT dan Biaya Modal.